2024
DOI: 10.5477/cis/reis.138.109
|View full text |Cite
|
Sign up to set email alerts
|

La corrupción en España (2004-2010): datos, percepción y efectos

Abstract: Los escándalos de corrupción investigados por los jueces han tenidogran presencia mediática en los últimos años en España. Ello podría habergenerado una percepción generalizada de incremento de la corrupcióny reforzado la desafección institucional. El objetivo de este artículoes analizar qué rasgos cuantitativos y cualitativos tiene la corrupción enEspaña y si la percepción correlaciona con los datos objetivos existentes.El texto parte de tres hipótesis. Para demostrarlas se han analizadoestadísticas judiciale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
6

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 0 publications
1
11
0
6
Order By: Relevance
“…Otro de los efectos es la tendencia del individuo a valorar más el carácter de los dirigentes que sus propias competencias. Por último, la generalización de la desconfianza, que puede llevar al ciudadano a la no participación de la vida política, (Thomson, 2003) o a la desafección institucional, generadora de un círculo vicioso de desconfianza que se autoalimenta (Villoria, 2012).…”
Section: La Comunicación Política Y La Corrupciónunclassified
“…Otro de los efectos es la tendencia del individuo a valorar más el carácter de los dirigentes que sus propias competencias. Por último, la generalización de la desconfianza, que puede llevar al ciudadano a la no participación de la vida política, (Thomson, 2003) o a la desafección institucional, generadora de un círculo vicioso de desconfianza que se autoalimenta (Villoria, 2012).…”
Section: La Comunicación Política Y La Corrupciónunclassified
“…In light of these examples, one may argue that the UP&LU recommendations that stem from our results will never be adopted, as the previous examples suggest that reductions in urban sprawl are against the main interest of local public authorities and private stakeholders. Given the large number of court cases in Spain in which local representatives and officials are accused of corruption and developers of bribery (Villoria and Jiménez ), we acknowledge that the recommendations that we offer will surely remain largely overlooked. But even if the results obtained in our study cannot be applied to past decisions, they can be used to plan present and future developments avoiding the larger provisions costs of planning low‐density, spatially extensive land use patterns.…”
Section: Economies Of Scale Urban Patterns and Optimal Population Dementioning
confidence: 99%
“…In contrast, other authors have found different evidence and argue that the perception of corruption is negatively related to satisfaction with democracy. Villoria and Jiménez (2012) found that those citizens in Spain who perceive that there is more corruption also have a lower satisfaction with democracy. Taking the latter into account H 6 : Those citizens who declare that they have a high level of support for and satisfaction with democracy are more likely to choose honest politicians than those with low levels of support and satisfaction.…”
Section: Participation and Political Culturementioning
confidence: 99%
“…This is so because in societies where there is distrust and citizens think that others will not act honestly, acting improperly becomes the rational thing to do, and thus distrust reinforces non-compliance with rules (Villoria and Jiménez, 2012). It is therefore expected that I Prefer the Corrupt One: A Profi le of Citizens who Choose Dishonest but Competent Politicians H 7 : Respondents with high levels of interpersonal trust are more likely to choose honest politicians than those citizens with low levels of interpersonal trust.…”
Section: Participation and Political Culturementioning
confidence: 99%